MOTIF DAN KENDALA BANK MELAKUKAN IMPLEMENTASI DINI PSAK NO. 71 TERHADAP CKPN KREDIT (MOTIVE AND OBSTACLE BANK AS EARLY ADOPTERS OF PSAK NO. 71 FOR ALLOWANCE FOR IMPAIRMENT LOSSES (CKPN) OF LOAN) - Rizal, Arya Prabu; Shauki, Elvia R. (UI Scholars Hub, 2019)
PSAK No. 71 convergence of IFRS 9 which will become effective on January 1, 2020, where early implementation is permitted. The complexity of this standard has caused several Banks not to carry out the impact assessment stage according to the OJK roadmap. However, there were Banks that had implemented before PSAK No. 71 effective (early adopters). This study applies a case study as its research strategy were content, thematic, and constant comparative analyses were used in analysing data collected from questionnaire and semi-structured interviews. This study found that several early adopters are Banks that are owned by the government, foreign, and joint venture banks. Besides, the author found that the motive in making the decisions to adopt/ not to adopt PSAK No. 71 is dominated by normative isomorphism as the pressures or demands being professional and considered right. This study also found that there are differences (heteregoneity) in the behavior of the actors and institutions in each bank that were influenced by multiple logics (i.e., rules as regulatory logics, and profit being the banking logics). This is done by the actors to maintain both logics by combining the two and looking at the external and internal factors of the institution.